Risk Security Cyber in System AI -Based : Study Evaluative on Indonesian Government Digital Infrastructure - Fauziyyah, Ghina; maulana, Indra; Komarudin, Komarudin; Selamet, Rachmat (Journal of Artificial Intelligence Research, 2025)
Digital transformation in sector the Indonesian government has push adoption technology intelligence artificial intelligence ( AI) wide , starting from service public until taking decision data- based . However , the development This accompanied with increasing complexity threat security cyber which is special target system AI -based research This aim For evaluate readiness government digital infrastructure in face risk security emerging cyber​ from use AI technology . The methods used is approach mixed - methods , with technique survey , interview in-depth , and study documentation to eight agency government centers and regions that have implement AI system . Research results show existence inequality between readiness adoption AI technology and protection security cyber . The most frequent threats found includes adversarial input, script injection, and social engineering against system administrators . Most of agency Not yet own policy or procedure technical specifically regulating​ mitigation risk AI security research This confirm importance compilation standard national security AI systems , HR training related to AI security, and implementation of algorithmic audits periodically in system government . With thus , the article This give contribution important in governance development​ security adaptive and responsive cyber​ to AI risks in the sector public .